2020
DOI: 10.1186/s12905-020-00898-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cognitive schemas on the mixed anxiety-depressive symptoms of breast cancer patients

Abstract: Background: The surgical treatment of breast cancer involves various psychological consequences, which differ according to individual characteristics. Our study aimed to identify the role that cognitive schemas had in triggering anxiety and depressive symptoms in patients diagnosed with breast cancer that underwent oncological and plastic surgery treatment. Methods: 64 female patients, diagnosed with breast cancer from an Oncology and Plastic Surgery Hospital, were selected to participate in this study between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Ethical clearance for the study was obtained from the Noguchi Memorial Institute of Medical Research, University of Ghana (NMIMR-IRB CPN 111/ [15][16]. Participants also gave.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical clearance for the study was obtained from the Noguchi Memorial Institute of Medical Research, University of Ghana (NMIMR-IRB CPN 111/ [15][16]. Participants also gave.…”
Section: Fundingmentioning
confidence: 99%
“…Young women living with breast cancer have more severe depression than older women [13]. These women have physical, psychological, and social concerns that require special care from a multidisciplinary healthcare professional [14,15]. Even though breast cancer comes with a myriad of challenges, studies indicate that when people are diagnosed with breast cancer, they gain personal strength out of their experiences, and become psychologically confident, emotionally mature, appreciate life, get closer to God, develop empathy for others and intimacy for family [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a study was published on the effect of early maladaptive schemas on anxiety symptoms. and mixed depression in breast cancer patients [13]. The study found that the early mastectomy schemes were activated in the sample that had mastectomy without plastic surgery, in contrast to the sample that had mastectomy with plastic surgery.…”
Section: The Previous Studiesmentioning
confidence: 84%
“…However, although a direct relationship between early, maladaptive schemas and breast cancer has not been proven, there are studies that have shown that there is a between early, maladaptive schemas and other variables that predict the trajectory of the disease, such as [3], which found a relationship between maladaptive early schemas and fear of cancer relapse and quality of life according to [6] and [7] mixed symptoms of anxiety and depression according to [13].…”
Section: A Discussing the First Questionmentioning
confidence: 99%
“…As a result, emotional discomfort and schema activation can lead to maladaptive relationships with oneself and others (Young, 1999). Indeed, within the literature, negative cognitive schemas have been associated with a broad array of harmful mental health outcomes, namely negative affect and depressive/anxiety symptoms (Bredicean et al, 2020;Faustino et al, 2022;Sellers et al, 2018), and particularly among individuals with substance use disorders (Shorey et al, 2015). To illustrate, within our present study, six EMSs (i.e., emotional deprivation, subjugation, failure, abandonment, mistrust, and social isolation) showed significant positive statistical correlations with drunkorexia scores.…”
Section: Discussionmentioning
confidence: 99%